Factors leading to surgical evacuation in first trimester medical termination of pregnancy - Mooppichathil, Rasila; Vaman, Jayshree V.; A., Simi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Aim of the study was to determine factors leading to surgical evacuation in first trimester medical termination of pregnancy of women attending SAT hospital, medical college, Thiruvananthapuram. Methods: A case control study was conducted at the department of obstetrics and gynaecology, Government Medical college, Thiruvananthapuram. The sample size was calculated to be 58 in each group. Antenatal women attending family planning OPD for termination of pregnancy in first trimester at SAT hospital over a period of one year were recruited for this study. A structured questionnaire was used to record history, examination findings, and investigations including ultrasound. The clinical outcome was defined as successful medical abortion and failed medical abortion which leads to surgical evacuation due to retained products. Results: Previous caesarean, previous induced abortion, previous pregnancy loss or increasing gestational age showed increasing rate of failed medical abortion. Also, in patients with anaemia with haemoglobin <11 gm/dl or diabetes or hypertension showed independent association with failed medical abortion. Conclusions: If patient planning for medical abortion, can do at earlier gestational age as advancing gestation will leads to increasing rate of failed medical abortion and also after correcting anaemia, with proper medication.